Standard Operating Procedure for Meteorology Early Warning System at BMKG Balikpapan - Gerry Muhammad Putra; Muhammad Gilvy Langgawan Putra (STMIK PONTIANAK, 2022)
Business process is a series of activities or steps in a business that converts one or more inputs into outputs. While the Standard Operating Procedure or SOP is a device that regulates the stages of a work process or activity then the device is standardized and documented so that it becomes a standard that applies to an organization. Meteorological Station Class 1 Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan is a government agency that provides weather forecast reports and is in charge of the meteorological department. In the service of the government agency, it has an application called the Meteorology Early Warning System. However, in using the application, a problem was found namely not all employees could operate the application correctly, and a standard was needed for the use of the application and that is Standard Operating Procedure (SOP), so the application can run smoothly. In making this SOP, there are methods, namely problem identification, conducting literature studies, collecting data, then the process identification and process discovery stages are carried out by following the standard business process management lifecycle, and finally making SOP documents. This research has produced an as-is business process model as many as 10 processes and SOP documents, namely the Account Installation and Control Process, the Weather Forecast Report Making Process, and the Monitoring Process with a total of 9 SOP documents. The SOP that has been made, must be evaluated considering future needs will be different from now